Pengaruh Penggunaan Dana Desa, Akuntabilitas dan Transparansi Pengelolaan Keuangan Desa Terhadap Kesejahteraan Masyarakat Desa Majasto Kecamatan Tawangsari - Hidayah Rukmana; Wikan Budi Utami; Darmanto (Nur Science Institute, 2023)
This study aims to determine the effect of the Use of Village Funds, Accountability, and Transparency of Village Finances on Community Welfare. This study uses a type of quantitative research with primary data with data collection techniques using questionnaires. The population in this study is all people in Majasto Village, totaling 4,377 people. The sampling technique was convenience sampling using the Slovin formula with a standard error of 10% so that a sample of 98 people was obtained and rounded up to 100 people. Data analysis used to process research data is descriptive statistical analysis, validity test, reliability test, classic assumption test. Testing the hypothesis using multiple linear analysis, F test, t test, and test the coefficient of determination (R2). The results of data processing using SPSS show that testing the regression model with the F test is feasible to use in this study. Then partially the use of village funds has a positive and significant effect on community welfare. Village financial accountability has a positive and significant effect on community welfare. Village financial transparency has a positive and significant effect on community welfare. Keywords: Village Funds, Accountability, Transparency, Community Welfare